Decellularized dermal matrices: unleashing the potential in tissue engineering and regenerative medicine - Rosadas, Marta; Silva, Inês V.; Costa, João B.; Ribeiro, Viviana P.; Oliveira, Ana L. (Frontiers in Materials, 2024)
Decellularized dermal matrices (dDMs) have emerged as effective biomaterials that can revolutionize regenerative medicine, particularly in the field of wound healing and tissue regeneration. Derived from animal or human skin, dDMs offer great biocompatibility, remarkable biochemistry, and a macromolecular architecture equivalent to the native tissue. Notably, among the biomimetic extracellular matrix (ECM)-based scaffolds, dDMs stand out due to their inherent dermal microenvironment, holding high value for skin regeneration and reconstructive surgery. The integration of dDMs as a biomaterial base for bioinks in advanced manufacturing technologies opens promising avenues for crafting precise, biomimetic tissue engineering (TE) constructs with optimized recellularization properties. This mini review outlines the main sources, differential decellularization techniques applied to dDMs, and their significance intissue engineering and regenerative medicine. It subsequently delves into the different categories of decellularized materials obtained, their unique physical and biochemical attributes, as well as their applications to promote wound healing and regenerating skin and soft tissues. Additionally, the currently available market products based on dDMs are examined and the main outcomes are compared. Finally, the article highlights current barriers in the field and anticipates the future challenges and applications of dDMs-based therapies.